Differential diagnosis of rheumatic manifestations of acromegaly. Case report - Margarita A. Perepelova; Larisa K. Dzeranova; Taras S. Panevin; Elena G. Przhiyalkovskaya; Ekaterina A. Pigarova; Ekaterina A. Troshina; Evgeniy G. Zotkin (Терапевтический архив)
Acromegaly is a chronic endocrine disease characterized by excessive secretion of growth hormone, which, in turn, leads to an increase in the secretion of insulin-like growth factor 1 in the liver. The targets for these hormones are most of the cells in our body. Excess growth hormone (in the vast majority of cases caused by hormone-producing pituitary adenoma – somatotropinoma), insulin-like growth factor leads to cellular, and tissue growth of almost all organs and systems, including the osteoarticular apparatus. Diagnosis of the disease in the early stages is often difficult and is established 5–10 years after the onset of symptoms, that leads to various complications and disability of patients. Often joint pain is the first manifestation of acromegaly. Damage to the musculoskeletal system causes a significant deterioration in the quality of life even when long-term stable remission of the underlying disease is achieved. In the article a clinical case with the peculiarities of diagnosing rheumatic disease in acromegaly is presented. A patient aged 56 years was diagnosed with acromegaly based on clinical and laboratory data, and a month later she underwent transnasal adenomectomy. However, Endocrinology Research Centre drew attention to the patient's complaints of pain in large joints, and therefore she was referred for a consultation to a rheumatologist at the Nasonova Research Institute of Rheumatology. As part of the examination, an increase in the titer of the antinuclear factor (1/2560) and the level of antibodies to ribonucleoprotein was revealed, which is most typical for mixed connective tissue disease. Treatment was prescribed and dynamic monitoring is being carried out.